Structural and Mechanistic Studies of Phosphoserine Aminotransferase - Ali, Fawad (fi=Turun yliopisto|en=University of Turku|, 2015)
Phosphoserine aminotrasferase (PSAT: EC 2.6.1.52) is a vitamin B6-dependent enzyme and a member of the subgroup IV in the aminotransferase superfamily. Here, X-ray crystallography was used to determine the structure of PSAT from Bacillus alcalophilus with pyridoxamine 5′-phosphate (PMP) at high resolution (1.57 Å). In addition, analysis of active residues and their conformational changes was performed. The structure is of good quality as indicated, for example, by the last recorded Rwork and Rfree numbers (0.1331 and 0.1495, respectively). The enzyme was initially crystallized in the presence of substrate L-glutamate with the idea to produce the enzyme-substrate complex. However, the structure determination revealed no glutamate bound at the active site. Instead, the Schiff base between Lys196 and PLP appeared broken, resulting in the formation of PMP owing to the excess of the donor substrate used during co-crystallization. Structural comparison with the free PSAT enzyme and the PSAR-PSER complex showed that the aromatic ring of the co-factor remains in almost the same place in all structures. A flexible nearby loop in the active site was found in the same position as in the free PSAT structure while in the PSAT-PSER structure it moves inwards to interact with PSER. B-factors comparison in all three structures (PSAT-PMP complex, free PSAT, and PSAT-PSER complex) showed elevated loop flexibility in the absence of the substrate, indicating that loop flexibility plays an important role during substrate binding. The reported structure provides mechanistic details into the reaction mechanism of PSAT and may help in understanding better the role of various parts in the structure towards the design of novel compounds as potential disruptors of PSAT function. This may lead to the development of new drugs which could target the human and bacterial PSAT active site.